2020
DOI: 10.48550/arxiv.2012.10323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Minimal generating sets for matrix monoids

F. Hivert,
J. D. Mitchell,
F. L. Smith
et al.

Abstract: In this paper, we determine minimal generating sets for several well-known monoids of matrices over certain semirings. In particular, we find minimal generating sets for the monoids consisting of: all n × n boolean matrices when n ≤ 8; the n × n boolean matrices containing the identity matrix (the reflexive boolean matrices) when n ≤ 7; the n × n boolean matrices containing a permutation (the Hall matrices) when n ≤ 8; the upper, and lower, triangular boolean matrices of every dimension; the 2 × 2 matrices ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Moreover, as φ 2 (Γ ′ ) = GL 2 (B) and GL 2 (B) is generated by φ 2 (A), we can see that φ 2 (A) ∪ φ 2 (γ) is a generating set for M 2 (S). However, this gives a contradiction as M 2 (S) is minimally generated by 3 matrices [9]. Therefore, M 2 (S) is minimally generated by these |X| + 2 matrices.…”
Section: × 3 Full Matrix Monoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as φ 2 (Γ ′ ) = GL 2 (B) and GL 2 (B) is generated by φ 2 (A), we can see that φ 2 (A) ∪ φ 2 (γ) is a generating set for M 2 (S). However, this gives a contradiction as M 2 (S) is minimally generated by 3 matrices [9]. Therefore, M 2 (S) is minimally generated by these |X| + 2 matrices.…”
Section: × 3 Full Matrix Monoidsmentioning
confidence: 99%
“…East, Jonušas and Mitchell [6] found generating sets for 2 × 2 full matrix monoids over the min-plus natural number semiring, max-plus natural number semiring, and their finite quotients. Moreover, Hivert, Mitchell, Smith, and Wilson [9] found minimal generating sets for a number of submonoids of the monoid of boolean matrices and showed that the generating sets given in [6] are minimal generating sets.…”
mentioning
confidence: 99%